I love the way you love me: Responding to partner's love language preferences boosts satisfaction in romantic heterosexual couples. - Olha Mostova; Maciej Stolarski; Gerald Matthews (PLoS ONE, 2022)
Chapman's Love Languages hypothesis claims that (1) people vary in the ways they prefer to receive and express affection and (2) romantic partners who communicate their feelings congruent with their partner's preferences experience greater relationship quality. The author proposes five distinct preferences and tendencies for expressing love, including: Acts of Service, Physical Touch, Words of Affirmation, Quality Time and Gifts. In the present study partners (N = 100 heterosexual couples) completed measures assessing their preferences and behavioral tendencies for a) expressions of love and b) reception of signs of affection, for each of the five proposed "love languages". Relationship satisfaction, sexual satisfaction and empathy were also assessed. The degree of the within-couple mismatch was calculated separately for each individual based on the discrepancies between the person's felt (preferred) and their partner's expressed love language. The joint mismatch indicator was a sum of discrepancies across the five love languages. Matching on love languages was associated with both relationship and sexual satisfaction. In particular, people who expressed their affection in the way their partners preferred to receive it, experienced greater satisfaction with their relationships and were more sexually satisfied compared to those who met their partner's needs to lesser extent. Empathy was expected to be a critical factor for better understanding of and responding to the partner's needs. Results provided some support for this hypothesis among male but not female participants.